On the status of Rossmaessleria scherzeri scherzeri (Zelebor in Pfeiffer & Zelebor, 1867) (Gastropoda: Pulmonata: Helicidae) - Neiber, Marco T. (Zootaxa, 2017)
The genus Rossmaessleria Hesse, 1907, belonging to a mainly North African radiation of land snails assigned to the tribe Otalini (Helicidae: Helicinae, see Razkin et al. 2015 and Neiber & Hausdorf 2015) has recently been subject to two independent revisions (Walther et al. 2016; Torres Alba et al. 2016). Torres Alba et al. (2016) provided a detailed re-description of the type species of Rossmaessleria, R. scherzeri (Zelebor in Pfeiffer & Zelebor, 1867), including an anatomical investigation. Additionally, Torres Alba et al. (2016) provided new data on several Moroccan taxa belonging to the genus, e.g. R. tetuanensis (Kobelt, 1881) and R. olcesei (Pallary, 1899). Walther et al. (2016) revised the taxa included in Rossmaessleria on the basis of an examination of all available type material and newly collected specimens and described several, conchologically distinct new taxa. These authors also examined genital anatomy, conducted phylogenetic analyses on the basis of mitochondrial sequences and used species delimitation approaches based on their molecular data, concluding that several conchologically distinct lineages can be recognized in Rossmaessleria, but that anatomical and genetic differentiation does not support the recognition of distinct species in the genus. This result was further corroborated by the presence, although infrequent, of conchologically intermediate forms between some of the Rossmaessleria taxa. Accordingly, Walther et al. (2016) recognized only a single species, R. scherzeri, with 11 subspecies, which are geographically restricted to isolated limestone ranges or outcrops in the western parts of the Rif Mountains in northern Morocco (ten subspecies) and to the Rock of Gibraltar, from where the nominotypical subspecies was described (Zelebor in Pfeiffer & Zelebor 1867).